Cross-country comparative analysis of social policy process: Implications for sustainable development in Vietnam - Hai, Do Phu (Edelweiss Applied Science and Technology, 2024)
This study explores how social policy institutions contribute to an "equal and fair society." Using Qualitative Comparative Analysis (QCA) on OECD and EU data, it examines six institutional conditions: election processes, transparency, civil rights, rule of law, executive capacity, and accountability. The findings highlight those strong democratic processes and robust institutional capacity are crucial for equitable outcomes. Vietnam’s socio-economic progress and challenges are analyzed to draw lessons for developing nations, emphasizing institutional reforms to enhance governance, equity, and sustainability. The study offers insights for policymakers to design inclusive and resilient social policies.